Ecosystem services provided by a non-cultured shellfish species: The common cockle Cerastoderma edule. (June 2020) - Carss, David N.; Brito, Ana C.; Chainho, Paula; Ciutat, Aurélie; de Montaudouin, Xavier; Fernández Otero, Rosa M.; Filgueira, Mónica Incera; Garbutt, Angus; Goedknegt, M. Anouk; Lynch, Sharon A.; Mahony, Kate E.; Maire, Olivier; et al.
Abstract: Coastal habitats provide many important ecosystem services. The substantial role of shellfish in delivering ecosystem services is increasingly recognised, usually with a focus on cultured species, but wild-harvested bivalve species have largely been ignored. This study aimed to collate evidence and data to demonstrate the substantial role played by Europe's main wild-harvested bivalve species, the common cockle Cerastoderma edule, and to assess the ecosystem services that cockles provide. Data and information are synthesised from five countries along the Atlantic European coast with a long history of cockle fisheries. The cockle helps to modify habitat and support biodiversity, and plays a key role in the supporting services on which many of the other services depend. As well as providing food for people, cockles remove nitrogen, phosphorus and carbon from the marine environment, and have a strong cultural influence in these countries along the Atlantic coast. Preliminary economic valuation of some of these services in a European context is provided, and key knowledge gaps identified. It is concluded that the cockle has the potential to become (i) an important focus of conservation and improved sustainable management practices in coastal areas and communities, and (ii) a suitable model species to study the integration of cultural ecosystem services within the broader application of 'ecosystem services'. Highlights: Cockles support ecosystems through water filtration and biogeochemical cycling. Cockles protect sediments, create habitats and support biodiversity within foodwebs. Cockles provide meat and shell by-products with potential value of €11.3M p.a. Cockles remove nitrogen, phosphorous, and carbon from the marine/estuarine environment. In coastal places, cockles are a bridge between ecosystem function and cultural values.